Evaluating congestion in urban areas: The case of Seville. (June 2021) - Christodoulou, A.; Christidis, P.
Abstract: We propose a methodology to measure the impact of congestion on accessibility at urban level using high-resolution population grid cells in combination with TomTom data on road congestion. The approach combines three accessibility indicators that can be calculated at different temporal and spatial levels of detail. The analysis of the impacts at fine resolution can reveal useful information as regards the segments of population to be affected by reduced accessibility. We test the approach using the urban area of Seville as a case study. The methodology can be generalized and applied in most urban areas in Europe and globally, since it uses standardized data on spatial definition, traffic data and population distribution. It therefore permits the comparison of the level and evolution of accessibility across different urban areas.